Hydroxychloroquine retinal toxicity in two patients with dermatological conditions. (2nd May 2018) - Kowalski, Tanya; Baker, Christopher; Mack, Heather G
Abstract: Two patients with dermatological conditions developed retinal toxicity after treatment with hydroxychloroquine that exceeded dosing recommendations. There is no treatment for hydroxychloroquine retinal toxicity and associated visual loss, so appropriate monitoring is imperative. All members of a patient's multidisciplinary team should be aware of the ocular risks of hydroxychloroquine, the importance of dosing within recommended guidelines and appropriate monitoring in reducing the risk of visual loss.